First evaluation of endotoxins in veterinary autogenous vaccines produced in Italy by LAL assay. (September 2018) - Di Paolo, Antonella; Forti, Katia; Anzalone, Lucia; Corneli, Sara; Pellegrini, Martina; Severi, Giulio; Cagiola, Monica
Abstract: Endotoxin contamination is a serious concern for manufacturers of biological products and vaccines in terms of not only quality but also safety parameters. We evaluated the endotoxin presence in different veterinary autogenous vaccines produced by the Pharmaceutical Unit at the Experimental Zooprophylactic Institute of Umbria and Marche "Togo Rosati" (IZSUM). According to the 3Rs principles (Replace, Reduce, Refine), which aim to progressively reduce animal use in the quality control process, we tested the vaccines obtained from gram-negative bacteria and adjuvants by the limulus amebocyte lysate (LAL) assay. The results revealed low endotoxin concentrations compared to available data in the literature and represent the first report of the application of the 3Rs principles to veterinary autogenous vaccines production in Italy.